Diseño y elaboración de un módulo de formación para la fe, para el grupo juvenil “Hijos De Dios”, de la parroquia “Nuestra Señora De La Inmaculada Concepción” de la parroquia Tumbaco - Pisuña Azaña, Rosa Elena (2013)
This thesis is an analysis of the situation of young people of the parish of Tumbaco. Not a pessimistic analysis, but realistically, that aims embodie din that reality in order to meet felt needs. The intervention is embodied in a module for animation work and missionary training of members of the youth group "Sons of God" of that Tumbaco. What motivates this work is the absence of a material that guarantees the formation of young people in the field of faith. In that sense, I want to provide a material having Christ as the cornerstone.